Telestroke management during the Hajj seasons 2023–2024: insights from SEHA Virtual Hospital in KSA - Alsaleh, Ghadah Sulaiman; Alhomod, Abdulaziz Suliman A.; Khan, Anas; Alzahrani, Saeed S. (Frontiers in Neurology, 2025)
BackgroundThe Hajj pilgrimage in Saudi Arabia poses significant healthcare challenges due to overcrowding and high demand. Stroke, a leading cause of morbidity and mortality, necessitates timely management, with telemedicine providing crucial remote access to specialized care.ObjectivesThis study aimed to evaluate the demographic and clinical characteristics of pilgrims who experienced strokes and utilized telemedicine during the Hajj seasons of 2023 and 2024, focusing on identifying changes in patient profiles and treatment patterns over time.Methods and materialsA cross-sectional study was conducted using data from SEHA Virtual Hospital (SVH) during the Hajj seasons of 2023 and 2024. The study included 459 adult stroke patients (207 in 2023 and 252 in 2024) who completed telemedicine consultations. Demographic and clinical data, including stroke types and treatment details, were retrospectively analyzed. Statistical comparisons were performed using chi-square and Mann–Whitney U tests, with significance set at p < 0.05.ResultsThe mean age of patients was 64.13 years in 2023 and 62.43 years in 2024. Non-Saudi patients constituted 69% in 2023, decreasing to 62% in 2024, while Saudi patients increased from 31 to 38%. Male patients rose from 57% in 2023 to 62% in 2024. Diagnoses showed significant variation: ischemic strokes increased from 46% in 2023 to 73% in 2024, while hemorrhagic strokes and other miscellaneous conditions decreased, and TIAs showed a slight increase. TPA administration remained stable at 23% in both years, and the median time to TPA administration showed no significant difference.ConclusionThe consistent application of a centralized telestroke service during the Hajj demonstrates that telemedicine is a viable and scalable strategy for delivering specialized stroke care in mass gathering settings. This model successfully managed a large, diverse patient cohort and maintained stable acute treatment rates, underscoring its potential to enhance health system resilience and equity during the most logistically challenging events.